1981
DOI: 10.1007/bf03186026
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of pylorus and rectal glands in Reduviidae (Insecta—Heteroptera)

Abstract: Anatomical and histological studies of the alimentary organs of sixteen reduviids, with diverse food habits indicate structural variations. The terminal part of the tubular second midgut of these predaceous insects has a permanent sac-like region with distinct histology, concerned with absorption of digested food. In addition, the digestive system is characterised by a reduced pylorus with pyloric-intestinal and pyloric-rectal valves, surrounded by flask-shaped ampullae of the four malpighian tubules. The ampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
2
7
1
Order By: Relevance
“…In contrast, proteins and peptides obtained by electrostimulation are produced in the posterior gland lumen and are likely to be used for predation as they potently paralyze and kill prey insects [96]. Similar functionally distinct compartments have been found in the main venom glands of other assassin bugs [101,102], although neither the role nor functional specialization of these compartments appears to be shared across all assassin bugs [103,104]. Interestingly, this venom system architecture is also shared with the homologous salivary glands of non-venomous non-heteropteran hemipterans, such as cicadas, where they are thought to perform different roles while feeding on plant sap [105], supporting the idea that this distinction is a morphological pre-adaptation that enables qualitative venom modulation.…”
Section: Venom Modulationmentioning
confidence: 99%
“…In contrast, proteins and peptides obtained by electrostimulation are produced in the posterior gland lumen and are likely to be used for predation as they potently paralyze and kill prey insects [96]. Similar functionally distinct compartments have been found in the main venom glands of other assassin bugs [101,102], although neither the role nor functional specialization of these compartments appears to be shared across all assassin bugs [103,104]. Interestingly, this venom system architecture is also shared with the homologous salivary glands of non-venomous non-heteropteran hemipterans, such as cicadas, where they are thought to perform different roles while feeding on plant sap [105], supporting the idea that this distinction is a morphological pre-adaptation that enables qualitative venom modulation.…”
Section: Venom Modulationmentioning
confidence: 99%
“…Previous studies have mostly focused on AMG and PMG, and empirical studies on different species have yielded inconsistent results. For instance, through toxicity assays, Haridass et al [15] studied the extracts of the different gland compartments of three assassin bug species and found that the AMG of these species were the primary source of venom used to paralyze the prey, and PMG secreted enzymes for the EOD. Combining the toxicity assay and proteomic and transcriptomic analysis, Walker et al [13] analyzed the roles of AMG and PMG extracts of Pristhesancus plagipennis (Reduviidae: Harpactorinae) during predation and defense.…”
Section: Introductionmentioning
confidence: 99%
“…horrida, the extent of involvement of these two chambers is context-dependent, with PMG responding to minor harassment and AMG to intensive harassment. Although the highly complex function of the main venom gland chambers from assassin bugs has been studied across several species [7,[13][14][15], the function of AG remains largely unexploited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. plagipennis PMG venom, which can be elicited by electrostimulation, paralyzed and killed their prey, whilst AMG venom, extracted via harassment, did not paralyze prey in the studied species [25]. However, paralytic effects of AMG venom were found in other assassin bug species [28]. AMG venom was suggested to serve defensive purposes and might deter common predators such as birds and small mammals [18,25].…”
Section: Introductionmentioning
confidence: 99%